Perancangan Sistem Telemetri Deteksi Bencana Banjir Berbasis Web Server Dan Sms Gateway - Hadi, Faisal; Rinaldi, Reza Satria; Supartian, Rahmat (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2020)
AbstractIndonesia is one of the areas prone to disasters, especially floods. The impact of flooding can be reduced if the community is better prepared to face the coming flood. Therefore we need an early flood detection tool that can give a signal to the community through early warning so that the community can be more alert in facing flood disastersThe results of this design make two systems, the main control system and the receiving system. The main control system consists of an ultrasonic sensor, SIM800L module and NodeMCU Wi-Fi module. The receiving system consists of a SIM800L module and a siren. The results showed that the ultrasonic sensor used has a good level of accuracy with an error value <1%. The results of SMS testing have a delay until the SMS to the recipient is around 5-10 seconds. The test results also show that 4G network technology has 100% delivery accuracy and 3-4 seconds delivery delay per data. The final result shows thatthe system is able to work as desired and is able to be well connected to the web server.Keyword:Flood Disasters, SIM800L, Ultrasonic sensor, Web Servers, SMS